Modeling And Simulation Of Plastic Wastes Generation For Operational Planning And Management In The Bonaberi Industrial Region, Cameroon - Ndoh Mbue, Innocent; Dieudonne, Bitondo (International Journal of Science, Technology & Management, 2022)
A review of waste management literature in use today shows that new techniques are needed in the process of planning strategic goals and objectives to technical goals and objectives. One of these techniques is the method which involves the modeling and simulation of wastes generated in our communities. This study uses the ARIMA (Autoregressive Integrated Moving Average), model to model and simulates plastic wastes generated in the Bonaberi industrial zone, of Cameroon for operational planning and management. Attention was also paid to their composition and uses as important resources for recycling industries. The monthly municipal plastic waste data from 2014 to 2020 was used to create a parsimonious ARIMA model. Different performance measures such as mean absolute deviation (MAD), mean absolute percentage error (MAPE), root mean square error (RMSE) and coefficient of determination (R-squared) were used to evaluate the performance of these models. Following this, ARIMA (1, 1, 1) model showed a superior prediction performance. According to this model, if current production and waste management trends continue, approximately 5468 Kg/month, 95% CI (2843, 9581) could be attained by December 2021.The results contribute to the process of planning strategic goals and objectives to technical goals and objectives in the region. The model developed can help decision-makers to take better measures and develop policies regarding waste management practices in the future. However, technical, environmental, and socio-economic feasibility studies to explore the technical options available, and to determine the factors that are considered important for the economic success of the project, and causing significant environmental problems resulting from improper disposal, namely burning or dumping, could also direct future investors in the region.